When the going gets tough, the tough get going: novel bacterial AAA+ disaggregases provide extreme heat resistance - Bohl, Valentin; Mogk, Axel (Environmental microbiology, 2024)
Heat stress can lead to protein misfolding and aggregation, potentially causing cell death due to the loss of essential proteins. Bacteria, being particularly exposed to environmental stress, are equipped with disaggregases that rescue these aggregated proteins. The bacterial Hsp70 chaperone DnaK and the ATPase associated with diverse cellular activities protein ClpB form the canonical disaggregase in bacteria. While this combination operates effectively during physiological heat stress, it is ineffective against massive aggregation caused by temperature-based sterilization protocols used in the food industry and clinics. This leaves bacteria unprotected against these thermal processes. However, bacteria that can withstand extreme, man-made stress conditions have emerged. These bacteria possess novel ATPase associated with diverse cellular activities disaggregases, ClpG and ClpL, which are key players in extreme heat resistance. These disaggregases, present in selected Gram-negative or Gram-positive bacteria, respectively, function superiorly by exhibiting increased thermal stability and enhanced threading power compared to DnaK/ClpB. This enables ClpG and ClpL to operate at extreme temperatures and process large and tight protein aggregates, thereby contributing to heat resistance. The genes for ClpG and ClpL are often encoded on mobile genomic islands or conjugative plasmids, allowing for their rapid spread among bacteria via horizontal gene transfer. This threatens the efficiency of sterilization protocols. In this review, we describe the various bacterial disaggregases identified to date, characterizing their commonalities and the specific features that enable these novel disaggregases to provide stress protection against extreme stress conditions.